Macedonian lionesses: Herakles and lion jewelry in elite female dress (c. 325–275 BCE) - Castor, Alexis Q. (Journal of Greek Archaeology, 2017)
Lions, of all animal quarry, rank among the most daunting and dangerous prey for hunters. Heroes and rulers demonstrated their physical strength in lion hunts and depicted them in historical records and images as a way to affirm their authority. Lions and the iconic lion-slayer Herakles, who was important in Macedonia as the ancestor of the royal Argead clan, became especially prominent in Late Classical and Early Hellenistic Macedonian art.